2014
DOI: 10.3928/02793695-20130930-05
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cognitive-Behavioral Therapy on Depression, Anger, and Self-Control for Korean Soldiers

Abstract: This quasi-experimental study examined the effects of cognitive-behavioral therapy (CBT) to control depression, anger, and self-control in soldiers from South Korea. Using a pretest-posttest design, the sample was composed of an experimental group (n = 16) and a control group (n = 12). The experimental group participated in four sessions of CBT. No significant differences were found between the groups with regard to demographic characteristics. Changes in the variables after the intervention were analyzed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
2
2
1
Order By: Relevance
“…In other words, we can state that the method of CBGT is effective in reducing depression of soldiers. Other studies have reported similar results that are in line with this study findings (4,(10)(11)(12)(22)(23)(24)(25). For example, Hyun et al showed that CBT is an effective treatment for depression in soldiers (22).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In other words, we can state that the method of CBGT is effective in reducing depression of soldiers. Other studies have reported similar results that are in line with this study findings (4,(10)(11)(12)(22)(23)(24)(25). For example, Hyun et al showed that CBT is an effective treatment for depression in soldiers (22).…”
Section: Discussionsupporting
confidence: 83%
“…Other studies have reported similar results that are in line with this study findings (4,(10)(11)(12)(22)(23)(24)(25). For example, Hyun et al showed that CBT is an effective treatment for depression in soldiers (22). Karlin et al showed CBT is an effective and acceptable treatment for older veterans in real environments with high depression level (23).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Considering that most of the stress from the military is related to the strict hierarchy and the top-down milieu, the first option of changing the situation itself is not likely to be realized [63]. Rather, it would be better to consider the second and third options; that is, a cognitive-behavioral approach to reevaluate the event from various perspectives or find the next best solution after accepting the situation [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the availability of several efficacious treatments for anxiety, including different forms of psychotherapy and pharmacotherapy (Cuijpers et al., ), literature tends to favour findings stemming from studies on the efficacy of psychotherapies and therapies provided by nurses (e.g. Asl & Barahmand, ; Hyun, Chung, De Gagne, & Kang, ) rather than those arising from studies on the efficacy of nursing psychotherapeutic interventions (interventions classified, for instance, on Nursing Interventions Classification [NIC]) (Bulechek, Butcher, Dochterman, & Wagner, ). Moreover, no studies were to be found in literature about the efficacy of psychotherapeutic interventions on anxiety as a symptom.…”
Section: Introductionmentioning
confidence: 99%